Analisis Efektivitas dan Kontribusi Pajak Daerah Sebagai Sumber Pendapatan Asli Daerah Provinsi DKI Jakarta - Havi, Alya Putri; Gurendrawati, Etty; Prihatni, Rida (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This study aims to analyze the effectiveness of Parking Tax, Land and Building Acquisition Duty (BPHTB), and Rural and Urban Land and Building Tax (PBB- P2) in increasing local tax contributions in 2019-2023. This research uses quantitative descriptive analysis method. The data used comes from the LKPD of DKI Jakarta Province in the form of targets and realization of local tax revenues, as well as the realization of Regional Original Revenue in 2019-2023. The results of this study indicate that the average level of effectiveness of Parking Tax is still in the less effective criteria of 79.55% and its contribution to PAD of 0.94% in the criteria is very less. Then, the average level of effectiveness of BPHTB is in moderately effective criteria of 81.18% and its contribution to PAD is 13.25% in the criteria of less. And the average level of effectiveness of PBB-P2 is quite effective at 89.47% and its contribution to PAD is 20.35% in moderate criteria.